ANALISIS PEMBENTUKAN KARAKTER RELIGIUS PADA TAHSIN DAN TAHFIDZ CAMP DI SMAI AL-AZHAR 19 CIRACAS - Windy Ajeng Kinanti; Fajar Syarif (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2023)
The Indonesian nation's character and religion are very well known. However, the rapid impact of globalization is slowly eroding this character. This failure occurred as a result of the ongoing educational process's neglect of morals. In facing changing circumstances and moral decline, students need religious character to be able to have and behave well in accordance with religious ideals. By establishing religious ideals to develop a religious personality in each student, school education plays an important role in determining personality and moral behavior. This paper aims to describe the analysis of the religious character of the tahsin and tahfidz camps at Al-Azhar 19 Ciracas Islamic High School. The source of this research is primary data sources obtained through direct observation at the school and Villa Degung Hillside Bogor, documenting activities that occur at the school and villa as a place for tahsin and tahfidz camps, as well as conducting interviews with the school principal, tahsin and tahfidz teachers, mentor Tahsin and Tahfidz and several students in grades 10, 11 and 12 at the school. Meanwhile secondary data was obtained from books, documents, journals, theses, data and articles obtained from the internet. This article shows that: success in forming religious character through tahsin and tahfidz study camps at SMAI Al-Azhar 19 Ciracas is demonstrated by attitudes and behavior that are obedient in carrying out the teachings of the religion one adheres to, tolerant towards the practice of worship of other religions and living in harmony with followers of other religions